Specific Features of Cultural and Religious varieties in the European Society - Olga Trofimova (Научно-аналитический вестник Института Европы РАН, 2019)
The article treats interconnections between European society and muslim diasporas which have their own cultural and religious traditions and customs. The author analyses specific features of integrating policies of migrants in various EU countries, its islamisation, problems of fragmentation of the European society and new approaches to integration of Muslim migrants.